Hubungan Menghafal Al-Quran dengan Kemampuan Bahasa Arab di Pesantren Dempo Darul Muttaqien - Yuniarti Yuniarti (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2020)
This research is motivated by the Arabic language education process on the relationship between Arabic and memorizing the Al quran which takes time, starting at the right time and ending when after reciting the meaning of the sentence in the verse of the Al quran. In the process of memorizing, namely writing down the verse, listening to the meaning and pronouncing it according to the rules. If the memorization process is done properly connecting Arabic and the Al quran correctly, the results will be good too. The purpose of memorizing the Al quran is to maintain the word of Allah Almighty by understanding the purpose and benefits of memorizing and besides being able to understand Arabic from existing verse fragments. After memorizing through the meaning of words, there will be an inhibiting factor in memorizing the Al quran for students of Dempo Darul Muttaqin Islamic Boarding School because students do not understand Arabic or students who cannot read the Al quran .This type of research is a qualitative study, namely a research procedure that produces data in the form of data collection in variables but sees it as part of a whole. In the data collection technique in this study, various techniques were used, using the method of observation, interviews and documentation. The data analysis procedure used in this research is qualitative analysis. The results of the research obtained the following results: how the relationship between learning Arabic and the memorization process has been done quite well, here it can be seen that there are various processes carried out by the school such as finding teachers who are competent in teaching, facilitating the media either the blackboard, the speakers used or a word guide book, either the Mahmud Yunus dictionary or the word Quran as a medium.